2019
DOI: 10.1177/1932296819883885
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reappraisal of the Time-in-Range: Alternative or Useful Addition to Glycated Hemoglobin?

Abstract: The HbA1c value is a well-established parameter used to characterize glucose control. Continuous glucose monitoring (CGM)-derived parameters calculated using daily glucose profiles such as Time-in-Range (TiR) have increasingly been gaining interest for assessing a patient’s current therapy. The question has arisen as to whether TiR could replace HbA1c? Because TiR focuses on the current quality of glucose control during a minimum of 10 to 14 days of CGM use and reflects the variability of glucose concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…A recent cross-sectional study conducting similar research in T1D neither found significant associations between TIR and carotid artery wall thickness or endothelial function [ 35 ]. Hence, our current findings are in favour of keeping HbA1c in the risk assessment for diabetic complications in T1D, complemented with instead of replaced by TIR, therefore we advocate for a multifactorial approach [ 36 ]. Indeed, it is expected that the landscape of glycemia management based on HbA1c is likely to change in favour of a more holistic approach considering all different aspects of dysglycemia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study conducting similar research in T1D neither found significant associations between TIR and carotid artery wall thickness or endothelial function [ 35 ]. Hence, our current findings are in favour of keeping HbA1c in the risk assessment for diabetic complications in T1D, complemented with instead of replaced by TIR, therefore we advocate for a multifactorial approach [ 36 ]. Indeed, it is expected that the landscape of glycemia management based on HbA1c is likely to change in favour of a more holistic approach considering all different aspects of dysglycemia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While CGM-derived metrics (eg, TiR and TaR) are becoming more and more popular in diabetes care, HbA1c is still the gold standard and most healthcare professionals are accustomed to its use as a reference parameter. Thus, the estimation of HbA1c from CGM plays the important role of enabling a smooth and increasing coaching of CGM in diabetes care, 33 by effectively relating its metrics to the well-consolidated use of HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters complementary to TIR are time spent with glucose values below 70 mg/dl, time below range (TBR), and time spent above 180 mg/dl, time above range (TAR). These parameters have some limits, related to the lack of an established standard for glucose measurement with CGM: as suggested by several authors, TIR should be regarded as a complement to HbA1c [77]. Indeed HbA1c values have been considered over the last decades the parameter that better correlates with clinical outcomes, even though additional evidence of a correlation between TIR and diabetes complications are emerging, both for micro and macrovascular complications [78][79][80].…”
Section: Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%